2014
DOI: 10.1002/ijc.29107
|View full text |Cite
|
Sign up to set email alerts
|

GLI2 is a novel therapeutic target for metastasis of osteosarcoma

Abstract: Aberrant activation of the Hedgehog (Hh) pathway has been reported in several malignancies. We previously demonstrated that knockdown of GLI2 inhibited proliferation of osteosarcoma cells through regulation of the cell cycle. In this study, we analyzed the function of GLI2 in the pathogenesis of osteosarcoma metastasis. Immunohistochemical studies showed that GLI2 was overexpressed in patient osteosarcoma specimens. Knockdown of GLI2 inhibited migration and invasion of osteosarcoma cells. In contrast, the forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
3
32
1
1
Order By: Relevance
“…Inhibition of the Hedgehog pathway has shown positive results when applied in cancer treatment. The inhibition of Gli-2 proved to be effective in osteosarcoma (20) and gastric cancer (18) as well as in non-surgical treatment of basal cell carcinomas (28). The findings of the present work, in conjunction with previously published data, can open the way for clinical studies analysing the performance of Hh Different letters represent significant findings (P < 0.05) between groups in each antibody studied (A, B).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Inhibition of the Hedgehog pathway has shown positive results when applied in cancer treatment. The inhibition of Gli-2 proved to be effective in osteosarcoma (20) and gastric cancer (18) as well as in non-surgical treatment of basal cell carcinomas (28). The findings of the present work, in conjunction with previously published data, can open the way for clinical studies analysing the performance of Hh Different letters represent significant findings (P < 0.05) between groups in each antibody studied (A, B).…”
Section: Discussionsupporting
confidence: 74%
“…As a progressive increase in the expression of all protein components of the Hedgehog pathway in AC and SCC was observed, it can be suggested that they do participate in the transformation of epithelial dysplasia to SCC of the lip. According to authors who have analysed Gli-2 function in osteosarcoma pathogenesis, some drugs like arsenic trioxide, vismodegib and GANT61, were able to inhibit the transcriptional activity of Gli-2 as well as migration and metastasis of osteosarcoma cells, confirming that Gli-2 regulates the transformation of this specific type of tumour (20). As a gradual increase of Gli-2 was seen in the cases studied in the present work, it is possible that this protein also has some participation in tumour transformation of lip SCC.…”
Section: Discussionmentioning
confidence: 91%
“…The Hedgehog pathway was initially recognized for its role in embryonic cell growth and differentiation and is involved in stem cell renewal, tissue regeneration, and tissue homeostasis [41]. It has also been found that Hedgehog signaling pathway was aberrantly activated which has been associated with initiation, proliferation, differentiation, migration of cell in several malignancies, including osteosarcoma cancer, gastric cancer, and so forth [42-44]. Activation of the canonical Hedgehog signaling cascade is mediated by three secreted ligands-Sonic Hedgehog (Shh), Indian Hedgehog (Ihh), and Desert Hedgehog (Dhh) and trans-membrane receptor Patched (Ptch), this activates another trans-membrane signaling molecule smoothened(Smo)[45].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that aberrant activation of Shh signaling is involved in a variety of cancers and disease states, playing an important role during tumor metastasis [52,55]. Recent studies have confirmed that aberrant activation of Shh signaling transduction is present in GBC [56][57][58].…”
Section: Hedgehog Signaling Pathwaymentioning
confidence: 95%